The disease burden of bladder cancer and its attributable risk factors in five Eastern Asian countries, 1990-2019: a population-based comparative study - Li-Sha Luo; Hang-Hang Luan; Ping Zhang; Jun-Feng Jiang; Xian-Tao Zeng; Jiao Huang; Ying-Hui Jin (BMC, 2024)
Abstract Backgrounds The study aimed to estimate bladder cancer burden and its attributable risk factors in China, Japan, South Korea, North Korea and Mongolia from 1990 to 2019, to discuss the potential causes of the disparities. Methods Data were obtained from the Global Burden of Disease Study 2019. The annual percent change (APC) and average annual percent change (AAPC) were calculated by Joinpoint analysis, and the independent age, period and cohort effects were estimated by age-period-cohort analysis. Results In 2019, the highest incidence (7.70 per 100,000) and prevalence (51.09 per 100,000) rates of bladder cancer were in Japan, while the highest mortality (2.31 per 100,000) and DALY rates (41.88 per 100,000) were in South Korea and China, respectively. From 1990 to 2019, the age-standardized incidence and prevalence rates increased in China, Japan and South Korea (AAPC > 0) and decreased in Mongolia (AAPC < 0), while mortality and DALY rates decreased in all five countries (AAPC < 0). Age effects showed increasing trends for incidence, mortality and DALY rates, while the prevalence rates increased first and then decreased in older groups. The cohort effects showed downward trends from 1914-1918 to 2004-2008. Smoking was the greatest contributor and males had the higher burden than females. Conclusion Bladder cancer was still a major public health problem in East Asia. Male and older population suffered from higher risk, and smoking played an important role. It is recommended that more efficient preventions and interventions should be operated among high-risk populations, thereby reduce bladder cancer burden in East Asia.